Digital 3D Brain MRI Arterial Territories Atlas - Chin-Fu Liu; Johnny Hsu; Xin Xu; Ganghyun Kim; Shannon M. Sheppard; Erin L. Meier; Michael I. Miller; Argye E. Hillis; Andreia V. Faria (Scientific Data, 2023)
Measurement(s) brain arterial territories Technology Type(s) Magnetic Resonance Imaging Factor Type(s) location Sample Characteristic - Organism Homo sapiens Sample Characteristic - Location United States of America